Genomic diversity of Ligularia revealed by complete plastid genomes and nuclear ribosomal DNAs from 16 collections in Korean Peninsula and Mt. Hallasan - Ju-Young Ahn; Seon Heui Jeong; Jong-Soo Kang; Jee Young Park; Yeon Jeong Kim; Yun Sun Lee; Jae Young Ko; Youn Gi Moon; Jung Hwa Kang; Tae-Jin Yang (PLoS ONE, 2026)
Plastid genome (plastome) and nuclear ribosomal DNA (nrDNA) sequences were assembled from 16 Ligularia accessions, including L. fischeri , L. fischeri var. spiciformis , and L. stenocephala . The assembled lengths ranged from 150,889 bp to 151,173 bp, while the 45S nrDNA transcription units varied from 5,846 bp to 5,848 bp. Comparative analyses revealed 0–106 SNPs and 0–60 InDels among the plastomes, and 1–50 SNPs and 0–4 InDels within the 45S nrDNA regions. Although the three taxa are morphologically distinct, phylogenetic analysis based on plastome and nrDNA sequences failed to differentiate them, with lineages from each taxon intermixing without clear separation. The incongruence between maternally inherited plastome- and biparentally inherited nrDNA-based phylogenies suggests frequent hybridization events, though incomplete lineage sorting may also contribute. This pattern of genetic admixture was also observed in accessions collected from various farms, implying that both natural and artificial hybridization have contributed to the current genetic structure. Samples from Mt. Hallasan showed broad genetic diversity, encompassing nearly all major variants found across the Korean Peninsula. Molecular markers were developed based on plastome variations and serve as grouping criteria. The genomic resources and markers generated in this study provide valuable tools for future molecular breeding and evolutionary research in Ligularia .